Study Correlation Wear Rate Measurement Technique of Flared Chisel Bucket Teeth Using 3D Scan Imaging and ASTM G105 - Budiwantoro, Bagus; Kurniawan, Kurniawan; Suratman, R.; Brodjonegoro, S.S (Mesin, 2017)
The aim of this study is searching a new method to provide wear rate measurement which simple and have better accuracy that occur in worn mining component surface addressed like flare chisel bucket teeth. Having correlation between Wet Sand Abrasion Test ASTM G105 and 3D scan modeling of worn surface, the validation of a new method to provide wear rate measurement using 3D scan technology would be elaborated. The preliminary study to provide wear rate measurement using 3D scan imaging have been established. The study related volume comparison by which 3d scan imaging process generated and buoyancy. Specimens were abraded using Wet Sand Abrasion Test ASTM G105 to provide specimen in certain percentage of volume loss. Several specimens consist of different percentage of volume loss were prepared. Specimens measured its volume over buoyancy and 3D scan imaging in two grade of meshing which are normal and smooth. Both of volume generated from 3D scan imaging compared to buoyancy volume measurement. Study focused on dissimilarity among volume data generated. Analysis are carried out through the center and variability both 3D scan volume compared to buoyancy volume. The study shows that normal meshing has less dissimilarity level compare to smooth meshing. Both dissimilarity level span at -0.01% and -0.027% respectively. Higher mesh level tends to inaccurate volume measurement. Further study to determine suitable mesh level should be conduct in near future.